A Study on Maxima and Minima for Single Real Valued Function - Pokhrel, Jagat Krishna (Tribhuvan University Journal, 2017)
By the maximum values of a function f (x) in calculus, we do not necessarily mean the absolutely greatest value attainable by the function. A function f (x) is said to be maximum for a value c of x, provided f (c) is greater than every other value assumed by f (x) in the immediate neighbourhood of x = c. Similarly a minimum value of f (x) is defined to be the value which is less than other values in the immediate neighbourhood.